النظائر المخادعة بين اللغة العربية واللغة السونداوية في قاموس اللغة السندوية لرادين ستشاديبراتا ودورها في تعليم اللغة العربية للمبتدئين السندويين - Hisan Mursalin (Rayah Al-Islam, 2019)
The purpose of this study is to reveal the Arabic and Sundanese vocabulary contained in the "Sundanese Dictionary" of the letters H to L, and their use in learning Arabic relevant to Sundanese students who are still in elementary level. Method of completing this research is literature review to know with main reference: Satjadibrata.R, Sundanese Dictionary. Kurnia.R, recognize the diversity of the Sundanese. The results in this study determine the meaning of Homonym is the same spelling word but different meaning. And Sundanese language as a communication tool used by the Sundanese, and as a tool of developers and supporters of Sundanese culture itself. Also set the ultimate goal in creating a Sundanese language dictionary to preserve the Sundanese language as a valuable heritage and to help anyone who wants to learn Sundanese. And this study also shows how to compare two vocabulary systems; namely by comparing the structure and form of the vocabulary of each language.